Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.3928/15428877-20070501-09
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab in Aggressive Posterior Retinopathy of Prematurity

Abstract: <P>The anatomic response to intravitreal bevacizumab injection in three patients with aggressive, posterior retinopathy of prematurity is described. In all cases, the worse eye was treated with a single intravitreal injection of 0.75 mg of bevacizumab as monotherapy or complementary to laser therapy. In 24 hours, all injected eyes showed regression of the tunica vasculosa lentis and iris vessel engorgement and disappearance of iris rigidity. In addition, plus disease and retinal proliferation began to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(40 citation statements)
references
References 21 publications
0
37
0
2
Order By: Relevance
“…VEGF, a hypoxia-induced cytokine, plays an important role in the normal development of retinal vasculature, in the involution of the HVS and in the development of ROP. 4 In the proliferative phase of ROP, retinal ischemia induces increased levels of VEGF, which leads to retinal NV and persistent TVL. 4 Clinically persistent TVL is often misdiagnosed as iris NV, 10 a condition in which newly formed vessels develop during the iris surface from the pupil margin to the iris root.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF, a hypoxia-induced cytokine, plays an important role in the normal development of retinal vasculature, in the involution of the HVS and in the development of ROP. 4 In the proliferative phase of ROP, retinal ischemia induces increased levels of VEGF, which leads to retinal NV and persistent TVL. 4 Clinically persistent TVL is often misdiagnosed as iris NV, 10 a condition in which newly formed vessels develop during the iris surface from the pupil margin to the iris root.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely-low-birth-weight (ELBW) and extreme prematurity are significant risk factors for candidemia 1,2 and retinopathy of prematurity (ROP), 3 in which retinal ischemia induces increased levels of vascular endothelial growth factor (VEGF) leading to retinal neovascularization (NV). 4,5 Studies have shown that candidemia in preterm infants can aggravate the severity of ROP, possibly to the threshold stage requiring laser treatment. 1,[6][7][8] Embryologically, the hyaloid vascular system (HVS) provides the blood supply to the posterior portion of the tunica vasculosa lentis (TVL), a transiently existing network of capillaries that functions to nourish the developing lens.…”
Section: Introductionmentioning
confidence: 99%
“…Za "pretreshold" stádium se považuje rozsah změn 3. stádia, které nedosahuje prahového stádia. Studie ETROP [16] 10,11,14,18,20,21,24,25,27,[31][32][33]38,41,44,47,50]. Ukazuje se, že léčba anti-VEGF preparáty umožňuje přiměřený vývoj vaskularizace sítnice a je spojena s nižším výskytem refrakčních vad a lepší výslednou zrakovou ostrostí.…”
Section: Indikace K Léčbě Ropunclassified
“…71,72 The use of the anti-VEGF agent Bevacizumab (Avastin; Genentech, South San Francisco, CA), a recombinant humanized anti-VEGF antibody was reported for use in ROP for the first time in the year 2007. 73,74 However, its use gained popularity after the randomized multicenter BEAT-ROP study which advocated its use in stage 3 ROP in zone 1 or posterior zone 2 ROP. 75 Since then there have been numerous reports of its success in the management of ROP as monotherapy, combination therapy with laser, as rescue therapy after failed laser photocoagulation or as an adjunct prior to vitrectomy.…”
Section: Anti -Vegf Therapy For Ropmentioning
confidence: 99%